2011
DOI: 10.1007/978-3-642-19890-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Learning from Demonstration

Abstract: Abstract.A model-free learning algorithm called Predictive Sequence Learning (PSL) is presented and evaluated in a robot Learning from Demonstration (LFD) setting. PSL is inspired by several functional models of the brain. It constructs sequences of predictable sensory-motor patterns, without relying on predefined higher-level concepts. The algorithm is demonstrated on a Khepera II robot in four different tasks. During training, PSL generates a hypothesis library from demonstrated data. The library is then use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Finally, it backs away from the pile and awaits more instructions. as a controller [21]. PSL is then able to repeat each of the three skills successfully, but unable to reproduce the complete load-transport-unload task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, it backs away from the pile and awaits more instructions. as a controller [21]. PSL is then able to repeat each of the three skills successfully, but unable to reproduce the complete load-transport-unload task.…”
Section: Discussionmentioning
confidence: 99%
“…This task is selected since the same data has previously been used to evaluate PSL as a controller [21]. In the previous evaluation, it was concluded that the PSL could learn each of the three skills (load, corridor and unload) but PSL was unable to repeat the overall task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Action selection where a function π selects a primitive π ∈ Π P : π = π (η ) (16) where π performs the mapping…”
Section: Learning With Behavior Primitivesmentioning
confidence: 99%